The Wonders of Cheetahs - Lantier, Patricia (Milwaukee, Wisconsin Gareth Stevens, 2001)
Readers will be intrigued by the sleek beauty and super speed of the cheetah.
K - 2
Keywords: Cheetah; Animal Wonders